Analysis of Factors Affecting Income Inequality in West Java 2012-2022 - Kusuma, Andita Delya; Machmud, Amir; Istikomah, Navik; Purnamasari, Imas; Mulyadi, Hari (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyze the effect of economic growth, human development index and labor on income inequality in West Java in 2012-2022. The method used in this research is a quantitative approach using secondary data in the form of panel data of 27 regencies or cities in West Java in 2012-2022 to be further analyzed using panel regression using EViews 12 with the Random Effect Model (REM) model. The results showed that simultaneously the variables of economic growth, human development index and labor had a significant effect on income inequality. While partially the economic growth variable has a positive and significant effect on income inequality, the human development index (HDI) has a positive and significant effect on income inequality, labor has a positive and insignificant effect on income inequality